Broadening the Use of the Concealed Information Test in the Field - Matsuda, Izumi; Ogawa, Tokihiro; Tsuneoka, Michiko (Frontiers in Psychiatry, 2019)
Japan is the only country where the polygraph with the concealed information test (CIT) is widely applied to criminal investigations. The CIT can reveal whether an examinee has knowledge of specific details of a crime. Furthermore, the CIT can extract crime-relevant information that investigative organizations have not yet uncovered. This article introduces how Japanese polygraphers take advantage of the CIT in criminal investigations. We also describe how polygraphs with the CIT are currently used in court. Then we propose statistical discrimination methods that can be easily applied to CIT interpretation in the field. Appropriate application of the statistical values is discussed. We hope that this article will facilitate more active use of the CIT outside Japan.